An Intervention Addressing Impostor Phenomenon in Undergraduate Physics and Astronomy - Ewan Bottomley; Paula Miles; Antje Kohnle; Vivienne Wild; Kenneth I. Mavor (Education Sciences)
The experience of the impostor phenomenon, when a person doubts themselves and believes that they are underqualified and do not belong in a position as a result, can be a challenge for undergraduate physics students. In a small-scale interview study, we found that the impostor phenomenon was frequently reported by physics undergraduates. On this basis, we developed an intervention to target the impostor phenomenon. The intervention had three phases. In the first phase, we introduced key concepts to students, giving them labels for their experiences. In the second phase, we gave students passages which depicted stories of higher-level students who had experienced the impostor phenomenon. We prompted conversation between students on the passages to normalize the discussion around the impostor phenomenon. Finally, in the third phase we asked students to reflect on what advice they would give future students who struggled with the impostor phenomenon. This was to encourage students to think about their own strategies when it comes to dealing with the impostor phenomenon. The intervention was run in class with 279 undergraduate students. The evaluation of the intervention via follow-up interviews was positive. The students spoke about the need for such an intervention and suggested adaptations. This intervention could be a step towards promoting a culture in educational settings where impostor feelings can be discussed openly.